Relevance of using both aerobic and anaerobic enrichment vials for optimizing rapid diagnosis of osteoarticular infections. (April 2022) - Coiffier, Guillaume; Ducasse, Emmanuelle; Keraudren, Arthur; Prat, Emilie; Modeste, Hortense; Albert, Jean-David; Loreal, Olivier; Guggenbuhl, Pascal; Jolivet-Gougeon, Anne
Abstract: The performance of a pair of blood culture vials (BACTEC® Plus Aerobic/F, and Anaerobic Lytic/F) were analyzed in 496 osteoarticular specimens (246 synovial fluids and 250 crushed bone samples), obtained in patients during routine diagnostic procedure at the Teaching Hospital of Rennes (France). The positive detection times were recorded for a 14 day-incubation period, and compared between both vials and with agar cultures. For samples from infected patients, the positive detection time was significantly shortened when vials were used compared to agar plates (p < 0.001). Median positive detection time was later with the Anaerobic Lytic/F vials (15.0 h) compared to the Plus Aerobic/F (13.0 h). Positivity rate was similar for Anaerobic Lytic/F vials (80.4%) and Plus Aerobic/F vials (83.2%) (p = 0.25). Some microorganisms were only identified from aerobic vials (15.5%) or from anaerobic vials (12.7%). The use of both atmosphere conditions for optimal positive detection time is therefore critical. Highlights: After 10 days of incubation, cases of contamination are most often observed. Use of a set of two vials is recommended to improve the rapidity of diagnosis. Positivity rate for anaerobic and aerobic vials was >80%.